2018
DOI: 10.5897/err2017.3407
|View full text |Cite
|
Sign up to set email alerts
|

Teachers opinions of human resources management functions in private schools

Abstract: In this research, teachers' opinions are determined based on human resources management functions in a private school. The research determined study groups with a purposive sampling method which is conducted with a qualitative research design, in the academic year, 2016 to 2017. Six teachers who work in a private school in Famagusta in Turkish Republic of Northern Cyprus (TRNC) participated in the study. The research data were collected by using a structure interview form and analyzed by content analysis and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Both individually and in groups in cooperation to achieve the goals of education. The elements in question are Human Resources (HR) (Öztürk, 2016), which consists of principals, teachers, staff, students or students, and students' parents (Merve & Cagda, 2018). Regardless of the role of other elements in the school organization, the top schools and teachers are internal personnel who have a role in creating the quality of education through learning activities; principals have an essential role to play in improving the work performance of teachers in schools (Lodesso et al, 2019;Sugilar, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Both individually and in groups in cooperation to achieve the goals of education. The elements in question are Human Resources (HR) (Öztürk, 2016), which consists of principals, teachers, staff, students or students, and students' parents (Merve & Cagda, 2018). Regardless of the role of other elements in the school organization, the top schools and teachers are internal personnel who have a role in creating the quality of education through learning activities; principals have an essential role to play in improving the work performance of teachers in schools (Lodesso et al, 2019;Sugilar, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This study is based on the results of research from Widiansyah et al, (2018) says that the demand for improving the quality of education implies the need for schools to have educational Human Resources, both educators and other human resources to perform optimally. Merve & Cagda (2018) continued that resource management includes; selection of educators/staff, training, and development, planning, evaluation, awarding. human resource management should reflect principles that strategically contribute to the expansion of student learning practices and societal boundaries, and skills development (Ranabahu & Almeida, 2019) Hidayat & Syam (2020) human resource management in the era of the industrial revolution 4.0 is an essential aspect of the education process.…”
Section: Introductionmentioning
confidence: 99%
“…Every principal as an organizational leader needs to master and have the ability to motivate his subordinates so that elementary school principals can influence their subordinates; they must understand their subordinates' needs. The success of school management is primarily determined by the activities of empowering human resources (HR) because the principal as a leader in an organization should be aware and responsive to be able to maintain teacher performance and job satisfaction by encouraging teachers to carry out their duties by the rules and regulations (Merve & Cagda, 2018;Yuliyati, 2020). Therefore, one of the principal's duties is to create professional teachers so that they can work by the directions given (Seriyanti et al, 2020) From the description above, it can be concluded that to optimize school management, it is necessary to do professionalism and teacher performance to find out the weaknesses and strengths that exist to improve and improve school management.…”
Section: Introductionmentioning
confidence: 99%